Symbolic Meaning of Dance Movement of Dagong Tradition of Indigenous People of Liong in the Village of Bantan Tengah Sub-District - Yosi Dwi Zulniati; Indrayuda Indrayuda (Science and Environmental Journal for Postgraduate, 2019)
This research aims to reveal, explain and analyze about: the symbolic meaning of the motion of Dagong dance, and the reason why the people still maintain the dance of Dagong tradition to date. This study uses a qualitative approach with a descriptive method. Data collection is done by observation, documentation and library study. Based on the research findings shows that (1) the symbolic meaning in the Dagong dance can be seen from each of the movements that have meaning and intent in it in the village of Bantan Tengah Sub-district of Bengkalis. Can be reviewed from the historical aspects of Dagong dance There is no change of movement from the past to the present, this dance is already empty because of the absence of dancers anymore. This dance is commonly performed by the indigenous peoples who were married and the event of seventeen Augustusan in the village to enliven. Then from the customary aspect of the existence of Dagong dance makes one that must be done if there is a ceremony of indigenous peoples Liong wedding party because this dance in the Sacred tribe think B Agi Indigenous Liong and there is a ritual process. (2) The process of implementation in the Ritual first by Bomo or the chief of the tribe, then when finished the event of new Ritunya dancers and musicians began to perform the dance. (3) The reason that society still maintains because this dance is a hereditary dance that is considered sacred by the indigenous people, although it is now almost extinct because of the absence of dancers anymore. And this dance is also a distinctive characteristic or self-identity, the original public ID of the tribe liong in village Bantan Central District BantanBengkalis District Riau Province